Novel gene mutation causing type 3 Von Willebrand disease: a case report and review of literature - Koneru, Shree H.; Raman, Shradha S.; Murugan, Swathi P.; Suman, Febe R.; Jayaraman, Dhaarani (International Journal of Contemporary Pediatrics, 2022)
Von Willebrand disease (VWD) Type 3 is an uncommon bleeding disorder, resulting from the near absence of Von Willebrand factor (VWF) and extremely low factor-VIII levels. It is a close differential diagnosis of hemophilia. A wide heterogeneity of VWD mutations are reported in the literature. We report a 16-year-old girl with hemarthrosis, finally diagnosed with Type 3 VWD. Clinical exome sequencing confirmed the diagnosis, revealing a homozygous mutation c.4387G>T (p. Glu1463Ter) in exon 28 of the VWF gene, a unique mutation not yet reported in the literature.